Insulin‐like growth factor binding protein‐2 and glucose‐regulated protein 78 kDa: Potential biomarkers affect prognosis in IDH‐wildtype glioblastoma patients - Harland, Abigail J.; Perks, Claire M.; White, Paul; Kurian, Kathreena M.; Barber, Hannah R. (Cancer medicine (Malden, MA), 2023)
Background The overall survival of IDH‐wildtype glioblastoma patients is poor despite best available treatments. There is an urgent need for new biomarkers to inform more precise disease stratification. Previous studies have identified insulin‐like growth factor binding protein‐2 (IGFBP‐2) as a potential biomarker for glioblastoma diagnosis and therapeutic targeting. Other studies have indicated links between the insulin‐like growth factor (IGF) axis and tumorigenic functions of a molecular chaperone glucose related protein of 78 kDa (GRP78). We aimed to interrogate the oncogenic effects of IGFBP‐2 and GRP78 in our glioma stem cell (GSC) lines and clinical cohort. Methods Immunoblotting, reverse transcription quantitative real‐time PCR were used to quantify protein and mRNA levels derived from GSCs and non‐malignant neural stem cells (NSCs). Microarray analysis was used to compare the differences in IGFBP‐2 (IGFBP‐2) and GRP78 (HSPA5) transcript expression between NSCs, GSCs and adult human cortex samples. Immunohistochemistry was used to quantify IGFBP‐2 and GRP78 expression in IDH‐wildtype glioblastoma tissue sections (n = 92) and clinical implications assessed using survival analysis. Finally, the relationship between IGFBP‐2 and GRP78 was further explored molecularly using coimmunoprecipitation. Results Here, we demonstrate that IGFBP‐2 and HSPA5 mRNA is overexpressed in GSCs and NSCs in comparison to non‐malignant brain tissue. We also determined a relationship in which G144 and G26 GSCs expressed higher IGFBP‐2 protein and mRNA than GRP78, and this was reversed in mRNA isolated from adult human cortex samples. Clinical cohort analysis revealed that Glioblastomas with high IGFBP‐2 protein expression paired with low GRP78 protein expression were significantly associated with a much shorter survival time (Median = 4 months, p = 0.019) compared with 12‐14 months for any other combination of high/low protein expression. Conclusions Inverse levels of IGFBP‐2 and GRP78 may be adverse clinical prognostic markers in IDH‐wildtype glioblastoma. Further interrogation of the mechanistic link between IGFBP‐2 and GRP78 may be important for rationalisation of their potential as biomarkers and therapeutic targets.